Effect of Angle of Incident on Angle of Reflection in Reflection of Light in a Plane Mirror - Chelseandara, Tarisa Virny; Wizayanti, Nabila Fairuz; Yanti, Elsa Dwi; Rahmadani, Nurlela Putri; Putri, Dwi Amelia; Nagifea, Friscella Yona; Sudarti, Sudarti; Baihaqi, Habibah Khusna (Jurnal Fisika Papua, 2025)
Light reflection is a basic phenomenon in optics that has been explained in depth in the law of light reflection. This law states that the angle of incidence of a light ray is equal to its angle of reflection when it hits a flat surface. Light reflection can occur on various surfaces, both smooth and rough. This study aims to experimentally corroborate the application of the law of light reflection on a flat mirror. The research method used is a quantitative method with an experimental design designed to measure the angle of incidence and angle of reflection of a laser beam directed at a flat mirror. This method allows researchers to collect numerical data that can be analyzed statistically. The results of the data analysis show that there is a linear relationship between the angle of incidence and the angle of reflection, with the values of the two angles always being equal for each measurement. This result is in line with the law of light reflection and provides strong evidence to support the correctness of the law.